2015
DOI: 10.1038/srep13058
|View full text |Cite
|
Sign up to set email alerts
|

Normal liver enzymes are correlated with severity of metabolic syndrome in a large population based cohort

Abstract: Key features of the metabolic syndrome are insulin resistance and diabetes. The liver as central metabolic organ is not only affected by the metabolic syndrome as non-alcoholic fatty liver disease (NAFLD), but may contribute to insulin resistance and metabolic alterations. We aimed to identify potential associations between liver injury markers and diabetes in the population-based Heinz Nixdorf RECALL Study. Demographic and laboratory data were analyzed in participants (n = 4814, age 45 to 75y). ALT and AST va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 56 publications
7
53
2
6
Order By: Relevance
“…Previous studies observed that vitamin D deficiency occurs more frequently in obese subjects than in normal body weight individuals [21] and that serum 25(OH)D and adiponectin concentrations are inversely correlated with BMI [39]. However, in this study, we could not replicate these findings.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies observed that vitamin D deficiency occurs more frequently in obese subjects than in normal body weight individuals [21] and that serum 25(OH)D and adiponectin concentrations are inversely correlated with BMI [39]. However, in this study, we could not replicate these findings.…”
Section: Discussioncontrasting
confidence: 56%
“…Numerous studies have suggested that a lower threshold for normal ALT could be better associated with liver or non-liver related morbidities [16,18,24]. In our study, we set the normal range according to manufacturer's recommendations and the individual R ratios were calculated accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider that liver pathologies can be silent and asymptomatic among subjectively healthy individuals [4, 13]; therefore, methods of liver protection while the liver is still relatively healthy are required.…”
Section: The Importance Of Liver Protection For Human Healthmentioning
confidence: 99%